Clinical features and outcomes of patients with Shwachman-Diamond syndrome and myelodysplastic syndrome or acute myeloid leukaemia: a multicentre, retrospective, cohort study. Issue 3 (March 2020) - Myers, Kasiani C; Furutani, Elissa; Weller, Edie; Siegele, Bradford; Galvin, Ashley; Arsenault, Valerie; Alter, Blanche P; Boulad, Farid; Bueso-Ramos, Carlos; Burroughs, Lauri; Castillo, Paul; Connelly, James; et al.
Summary: Background: Data to inform surveillance and treatment for leukaemia predisposition syndromes are scarce and recommendations are largely based on expert opinion. This study aimed to investigate the clinical features and outcomes of patients with myelodysplastic syndrome or acute myeloid leukaemia and Shwachman-Diamond syndrome, an inherited bone marrow failure disorder with high risk of developing myeloid malignancies. Methods: We did a multicentre, retrospective, cohort study in collaboration with the North American Shwachman-Diamond Syndrome Registry. We reviewed patient medical records from 17 centres in the USA and Canada. Patients with a genetic (biallelic mutations in the SBDS gene) or clinical diagnosis (cytopenias and pancreatic dysfunction) of Shwachman-Diamond syndrome who developed myelodysplastic syndrome or acute myeloid leukaemia were eligible without additional restriction. Medical records were reviewed between March 1, 2001, and Oct 5, 2017. Masked central review of bone marrow pathology was done if available to confirm leukaemia or myelodysplastic syndrome diagnosis. We describe the clinical features and overall survival of these patients. Findings: We initially identified 37 patients with Shwachman-Diamond syndrome and myelodysplastic syndrome or acute myeloid leukaemia. 27 patients had samples available for central pathology review and were reclassified accordingly (central diagnosis concurred with local in 15 [56%] cases), 10 had no samples available and were classified based on the local review data, and 1 patient was excluded at this stage as not eligible. 36 patients were included in the analysis, of whom 10 (28%) initially presented with acute myeloid leukaemia and 26 (72%) initially presented with myelodysplastic syndrome. With a median follow-up of 4·9 years (IQR 3·9–8·4), median overall survival for patients with myelodysplastic syndrome was 7·7 years (95% CI 0·8–not reached) and 0·99 years (95% CI 0·2–2·4) for patients with acute myeloid leukaemia. Overall survival at 3 years was 11% (95% CI 1–39) for patients with leukaemia and 51% (29–68) for patients with myelodysplastic syndrome. Management and surveillance were variable. 18 (69%) of 26 patients with myelodysplastic syndrome received upfront therapy (14 haematopoietic stem cell transplantation and 4 chemotherapy), 4 (15%) patients received no treatment, 2 (8%) had unavailable data, and 2 (8%) progressed to acute myeloid leukaemia before receiving treatment. 12 patients received treatment for acute myeloid leukaemia—including the two patients initially diagnosed with myelodysplastic who progressed— two (16%) received HSCT as initial therapy and ten (83%) received chemotherapy with intent to proceed with HSCT. 33 (92%) of 36 patients (eight of ten with leukaemia and 25 of 26 with myelodysplastic syndrome) were known to have Shwachman-Diamond syndrome before development of a myeloid malignancy and could have been monitored with bone marrow surveillance. Bone marrow surveillance before myeloid malignancy diagnosis was done in three (33%) of nine patients with leukaemia for whom surveillance status was confirmed and 11 (46%) of 24 patients with myelodysplastic syndrome. Patients monitored had a 3-year overall survival of 62% (95% CI 32–82; n=14) compared with 28% (95% CI 10–50; n=19; p=0·13) without surveillance. Six (40%) of 15 patients with available longitudinal data developed myelodysplastic syndrome in the setting of stable blood counts. Interpretation: Our results suggest that prognosis is poor for patients with Shwachman-Diamond syndrome and myelodysplastic syndrome or acute myeloid leukaemia owing to both therapy-resistant disease and treatment-related toxicities. Improved surveillance algorithms and risk stratification tools, studies of clonal evolution, and prospective trials are needed to inform effective prevention and treatment strategies for leukaemia predisposition in patients with Shwachman-Diamond syndrome. Funding: National Institute of Health.